Integrated weed management in bush type vegetable cowpea(Vigna unguiculata subsp.unguiculata(L.) Verdcourt - Sinchana J K (Department of Agronomy, College of Agriculture, 2020)
The study entitled “Integrated weed management in bush type vegetable cowpea (Vigna unguiculata subsp. unguiculata (L.) Verdcourt) was carried out during the period 2018-2020, at College of Agriculture, Vellayani, Thiruvananthapuram, Kerala with an objective to find out a cost-effective weed management practice for bush type vegetable cowpea. The field experiment was undertaken at Coconut Research Station, Balaramapuram, Thiruvananthapuram, Kerala during Kharif 2019 (May to August 2019). The experiment was conducted in RBD with two factors, first factor being seed bed preparation (S), viz., stale seed bed (S1) and normal seed bed (S2) and second factor, weed management practices (W) viz., dried banana leaf mulch @ 10 t ha-1 alone (W1), dried banana leaf mulch @ 10 t ha-1 fb post emergence imazethapyr @ 50 g ha-1 at 25 DAS (W2), dried banana leaf mulch @ 10 t ha-1 fb post emergence quizalofop-p-ethyl @ 50 g ha-1 at 25 DAS (W3), post emergence imazethapyr @ 50 g ha-1 at 15 DAS (W4), pre emergence diclosulam @ 12.5 g ha-1 fb post emergence quizalofop-p-ethyl @ 50 g ha-1 at 25 DAS (W5), pre emergence diclosulam @ 12.5 g ha-1 fb hand weeding at 25 DAS (W6), hand weeding at 20 and 40 DAS (W7) and weedy check (W8). The variety used for the study was Bhagyalakshmy. Results of the experiment revealed that stale seed bed (SSB) had significant effect on crop growth parameters, physiological parameters, total chlorophyll content and nodule parameters at different stages of crop and it recorded the lowest total weed density and nutrient removal by weeds, the highest WCE, total plant uptake, yield, net income, harvest index, B: C ratio and the lowest weed index. Weed management practices significantly influenced the growth, physiological, and nodule parameters at different stages of crop growth. The treatments W2, W3 and W1 recorded the lowest total weed density and the treatments W6, W7 and W3 recorded the highest weed control efficiency at 15, 30 and 45 DAS, respectively. The N, P and K uptake by weeds at 30 and 45 DAS was recorded the lowest in W7 and W3, respectively. Results 200 on dehydrogenase and urease enzyme activity revealed that the tested herbicides, viz., diclosulam, imazethapyr and quizalofop-p-ethyl did not have any negative impact. The treatment w3 recorded the highest N and P uptake by crop, pods per plant (44.00), pod length (15.23 cm), pod girth (2.20 cm), pod weight (2.56 g), green pod yield per plant (110.73 g) and per hectare (7589.0 kg), net income (₹63,121.0), B:C ratio (1.71) and the lowest weed index (1.68 per cent). The treatment w6 recorded the highest K uptake by crop and protein content the highest in W1. The interaction effect was significant for leaves per plant at 60 DAS, root fresh weight, root volume and LAI at 20 and 60 DAS, chlorophyll content at 40 and 60 DAS and nodule parameters at 50 per cent flowering stage. The lowest total weed density was registered in s1w5, s1w3 and s1w2 at 15, 30 and 45 DAS, respectively. The treatment s1w6 recorded the highest weed control efficiency at 15 and 45 DAS and s1w7 at 30 DAS. The weed index was recorded the lowest in s1w3. At 30 and 45 DAS, s2w8 recorded the highest N, P and K uptake by weeds. The number of green pods per plant (44.7), pod weight (2.68, g), pod yield per plant (119.66 g) and per hectare (7731.7 kg), harvest index (0.279), net income (₹ 64,775.0) and B: C ratio (1.72) were found the highest in s1w3. The protein content was recorded the highest in s1w1. Hence, considering the WCE, yield, weed index, HI, net income and B:C ratio, stale seed bed + dried banana leaf mulch 10 t ha-1 fb application of quizalofop-p-ethyl @ 50 g ha-1 at 25 DAS (s1w3) could be adjudged as the cost effective and the best weed management practice for higher green pod yield and net return in bush type vegetable cowpea.